2021
DOI: 10.3389/fdmed.2020.623768
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Malocclusion and Academic Performance Among Mongolian Adolescents

Abstract: Objective: Malocclusion has been reported to affect the daily lives of schoolchildren adversely, but little is known regarding the association between malocclusion and academic performance. We aimed to investigate the association between malocclusion and academic performance among adolescents in Mongolia.Methods: We conducted a cross-sectional study of 767 students aged 7–16 years from two public schools in Ulaanbaatar, Mongolia. Three orthodontists evaluated the need for malocclusion treatment in the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Eight studies 10,[21][22][23][24][25][26][27] were included in the qualitative synthesis, and their outcomes are summarized below.…”
Section: Summary Of Measurements and Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies 10,[21][22][23][24][25][26][27] were included in the qualitative synthesis, and their outcomes are summarized below.…”
Section: Summary Of Measurements and Synthesis Of Resultsmentioning
confidence: 99%
“…As for the perception of parents, 77% felt that the school performance of their children was affected by dental appearance, 79% of teachers reported such perception, and 32.7% of the close friends of the students analyzed mentioned such a relationship. Badrakhkhuu et al 27 also observed that schoolchildren in Mongolia with dental crowding, a type of malocclusion, might be prone to poor academic performance, particularly in arts and physical education.…”
Section: Summary Of Measurements and Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study involved children (aged between 5 and 16 years), randomly selected from each year group from the 1st to 10th grades. Further details concerning the survey have been published elsewhere [ 25 , 26 , 27 , 28 ]. This study was approved by the Ethical Review Board of the MNUMS (No.…”
Section: Methodsmentioning
confidence: 99%